Theranostic Terbium Radioisotopes: Challenges in Production for Clinical Application - Naskar, Nabanita; Lahiri, Susanta (Frontiers in Medicine, 2021)
Currently research on terbium has gained a momentum owing to its four short-lived radioisotopes, 149Tb, 152Tb, 155Tb, 161Tb, all of which can be considered in one or other field of nuclear medicine. This emerging quadruplet family have appealing nuclear characteristics and has the potential to do justice to the proposed theory of theranostics nuclear medicine, which amalgamates therapeutic and diagnostic radioisotopes together. The main challenge for in vivo use of these radioisotopes is to produce them in sufficient quantity. This review discusses that at present neither light charged particle nor the heavy ion (HI) activation are suitable for large-scale production of neutron deficient terbium nuclides. Three technological factors like (i) enrichment of stable isotopes to considerable level, (ii) non-availability of higher energies in commercial cyclotrons (iii) non-availability of isotope separation technique coupled with commercial accelerators limit the large scale production of terbium radionuclides by light charged particle activation. If in future, the technology can overcome these hurdles, then the light charged particle activation of enriched targets would produce high amount of useful terbium radionuclides. On the other hand, till date, the spallation reaction coupled with online isotope separator has been found suitable for such requirement, which has been adopted by the CERN MEDICIS programme. The therapeutic 161Tb radionuclide can be produced in a reactor by neutron bombardment on enriched 160Gd target to produce 161Gd which subsequently decays to 161Tb. The radiochemical separation is mandatory even if the ISOL technique is used to obtain high radioisotopic purity of the desired radioisotope.